Ethyl 2-(12-Oxo-10,12-dihydroisoindolo[1,2-b] Quinazolin-10-yl) Acetate - Valerio Morlacci; Massimiliano Aschi; Marco Chiarini; Antonio Massa; Antonio Arcadi; Laura Palombi (Molbank, 2023)
The title compound has been synthetized using a one-pot cascade process of ethyl (E)-3-(2-aminophenyl) acrylate and 2-formylbenzonitrile in the presence of Cs2CO3 as the catalyst. The synthetic route has been rationalized as a base-catalyzed tandem addition/cyclization/rearrangement initiated by the aniline molecule, followed by sequential aza-Michael addition/dehydrogenation. A theoretical investigation also provided a rationale for its fluorescence properties.